Melatonin supplementation for the treatment of infantile spasms: protocol for a randomised placebo-controlled triple-blind trial. Issue 7 (4th July 2022) - Sun, Yulin; Feng, Weiwei; Chen, Jian; Liu, Miao; Shi, Xiuyu; Wang, Jing; Zou, Liping; Xu, Tao; Yang, Guang
Abstract : Introduction: Infantile spasms (IS) is a type of severe epileptic encephalopathy that occurs in infancy and early childhood. IS is characterised clinically by epileptic spasms, often accompanied by sleep disorder and abnormal circadian rhythm. The endogenous circadian rhythm disorder, in turn, can make spasms worse. Melatonin has also been found to have anticonvulsant and neuroprotective properties by adjusting the circadian rhythm. However, there are lack of relevant studies on controlling IS by using melatonin. This study aims to analyse the therapeutic effect of melatonin supplementation for the treatment of IS. Methods and analysis: This is a triple-blinded (trial participant, outcome assessor and the data analyst), prospective, randomised controlled trial to be conducted in the Department of Paediatrics, The First Medical Center of Chinese PLA General Hospital, Beijing, China from November 2020. Patients (n=70) aged 3 months to 2 years with IS will be recruited in this study after receiving written consent from their parents or guardians. Patients will be randomly divided into two equal groups and treated with a combination of adrenocorticotropic hormone, magnesium sulfate and either melatonin or placebo. Clinical data from the patients in the two groups before and after the treatment will be collected and compared. The primary outcome will be assessed 2 weeks later by seizure diaries and reported as the average reduced rate of spasms frequency. Secondary outcomes include the response rate (the rate of spasms-free), electroencephalogram hypsarrhythmia assessment and the psychomotor development assessment (Denver Developmental Screening Test). Sleep quality and safety will also be assessed. Ethics and dissemination: The protocol for this study was approved by the Ethics Committee of Chinese PLA General Hospital (reference number S2020-337-01) and was reported according to the Standard Protocol Items: Recommendations for Interventional Trials statement. Findings of this research will be disseminated through national and international meetings, conferences and peer-reviewed journals. Trial registration number: ChiCTR2000036208.